Loss of KCC2 in GABAergic Neurons Causes Seizures and an Imbalance of Cortical Interneurons - Zavalin, Kirill; Hassan, Anjana; Fu, Cary; Delpire, Eric; Lagrange, Andre H. (Frontiers in Molecular Neuroscience, 2022)
K-Cl transporter KCC2 is an important regulator of neuronal development and neuronal function at maturity. Through its canonical transporter role, KCC2 maintains inhibitory responses mediated by aminobutyric acid type A (GABA) receptors. During development, late onset of KCC2 transporter activity defines the period when depolarizing GABAergic signals promote a wealth of developmental processes. In addition to its transporter function, KCC2 directly interacts with a number of proteins to regulate dendritic spine formation, cell survival, synaptic plasticity, neuronal excitability, and other processes. Either overexpression or loss of KCC2 can lead to abnormal circuit formation, seizures, or even perinatal death. GABA has been reported to be especially important for driving migration and development of cortical interneurons (IN), and we hypothesized that properly timed onset of KCC2 expression is vital to this process. To test this hypothesis, we created a mouse with conditional knockout of KCC2 in Dlx5-lineage neurons (Dlx5 KCC2 cKO), which targets INs and other post-mitotic GABAergic neurons in the forebrain starting during embryonic development. While KCC2 was first expressed in the INs of layer 5 (L5) cortex, perinatal IN migrations and laminar localization appeared to be unaffected by the loss of KCC2. Nonetheless, the mice had early seizures, failure to thrive, and premature death in the second and third weeks of life. At this age, we found an underlying change in IN distribution, including an excess number of somatostatin neurons in L5 and a decrease in parvalbumin-expressing neurons in L2/3 and L6. Our research suggests that while KCC2 expression may not be entirely necessary for early IN migration, loss of KCC2 causes an imbalance in cortical interneuron subtypes, seizures and early death. More work will be needed to define the specific cellular basis for these findings, including whether they are due to abnormal circuit formation versus the sequela of defective IN inhibition.